Food safety knowledge, attitude, and practices of street food vendors in Naga City, Camarines Sur, Bicol Region - De Lima, Marie Danilyn D. (College of Home Economics, University of the Philippines Diliman, 2023)
Street foods are affordable foods and beverages that are readily sold on the streets. However, these are susceptible to contamination due to improper food handling, and may lead to foodborne illnesses. This study looked into the knowledge, attitude, and practices (KAP) of street food vendors (n=42) in Naga City, Camarines Sur, and to determine if there are significant differences between the vendors’ socio-demographic characteristics and their KAP. A survey questionnaire consisting of four sub-sections: (1) demographic information of the street food vendors, (2) knowledge of food safety, (3) attitude towards food safety, and (4) the performed food safety practices of the street food vendors, were given out to the respondents. The food safety knowledge, attitude, and practices of the street food vendors were found to be of moderate, good, and positive levels, respectively. Specifically, 42.9% have limited knowledge regarding food safety, 83.3% have good attitude towards food safety, and 100% of the respondents report that they practice the right food handling techniques. Only the respondents’ sex and their attitudes were found to have significant differences. The results suggest the need to improve the street food vendors' knowledge through intensive training, and to translate these into attitudes and strict observance of practices to guarantee the safety of the food prepared.